Effects of transcranial direct current stimulation combined with acupuncture therapy on brain network functional connectivity in patients with knee osteoarthritis: a single-center randomized controlled trial - Qiu Nie; Fang He; Linghui Dong; Xikai Lin; Jingyi Lin; Yinxu Wang; Yulei Xie (Journal of NeuroEngineering and Rehabilitation)
Abstract Background In this study, we investigated the effects of transcranial direct current stimulation (tDCS) combined with acupuncture therapy on pain, dysfunction and functional connectivity in patients with knee osteoarthritis (KOA), and to evaluate its potential therapeutic value. Method In this single-center, randomized controlled trial, patients were recruited from May 2023 to August 2024 from the Departments of Rehabilitation, Orthopedics, and Pain Management at the Affiliated Hospital of North Sichuan Medical College. The patients were randomly assigned to three groups, including the acupuncture group, the tDCS group, and the combined acupuncture and tDCS group. All treatments were administered five times a week for two weeks. The condition of the patients was evaluated by the visual analog scale (VAS), the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), the Lequesne index, and functional near-infrared spectroscopy (fNIRS) before treatment and after two weeks of treatment, respectively. Results In total, 63 patients were enrolled and randomly assigned to three groups. Three patients were excluded for work-related reasons, fear of acupuncture, or time conflicts repectively, which prevented further follow-up. The VAS score, WOMAC score, and Lequesne indexes of all patients were significantly lower after treatment than before treatment (P < 0.01). Compared to the tDCS group and the acupuncture group, the combined group showed greater improvements in the VAS score, WOMAC score, and Lequesne indexes (P < 0.05). The fNIRS results indicated a significant reduction in the mean cerebral functional connectivity strength based on oxyhemoglobin (HbO2) and deoxyhemoglobin (HbR) across all three groups following treatment (P < 0.05). The functional connectivity strengths of the HbO2-based LPFC ~ LPFC, RPFC ~ RPFC, LMC ~ LMC, RMC ~ RMC, LPFC ~ RPFC, LPFC ~ LMC, LPFC ~ RMC, RPFC ~ LMC, RPFC ~ RMC, LMC ~ RMC; HbR-based LPFC ~ LPFC, RPFC ~ RPFC, LMC ~ LMC, RMC ~ RMC, LPFC ~ LMC, LPFC ~ RMC and LMC ~ RMC in the combined group were significantly lower than those in the acupuncture group (P < 0.05).The HbO2-based LPFC ~ LPFC, RPFC ~ RPFC, LMC ~ LMC, and RMC ~ RMC in the combined group were significantly lower than those in the tDCS group (P < 0.01). Compared to those in the acupuncture group, the HbR-based LPFC ~ LPFC and LMC ~ LMC of the patients in the tDCS group were lower (P < 0.05). Conclusions The combination therapy of tDCS and acupuncture is better than monotherapy in relieving pain and dysfunction in patients with KOA. The improvement in efficacy may be related to the reduction in brain functional connectivity and may become a new treatment method for treating KOA. Trial registration ChiCTR2300073819.